PENDIDIKAN TEORI TENTANG PENEMUAN HUKUM DAN PENCIPTAAN HUKUM BAGI MAHASISWA ILMU HUKUM DAN ILMU SOSIAL - Adnani, Adriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Students of law and social sciences should not be contradicted between legal discovery and law creation because both of them use logic to find legal conclusions in concreto. The creation of law (rechtsschepping) is carried out through legal discovery by using certain methods in the form of analogies, argumentum a contrario, and legal refinement (vervijning); whereas legal discovery (rechtsvinding) is carried out by interpretation method. The use of the method of discovering the law and the creation of law is expected to produce a court ruling that has authoritative value. So that court decisions can be the primary legal material in legal research.